2021
DOI: 10.1186/s12903-021-01655-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of deubiquitinases in human gingiva and cultured human gingival fibroblasts

Abstract: Background Although deubiquitinating enzymes (DUBs) such as CYLD, A20 and OTULIN are expressed in multiple tissues and thought to be linked with inflammatory diseases, their expression in periodontal tissues remains to be determined. This research was designed to assess the expression of CYLD, A20 and OTULIN in human gingiva, and to evaluate the regulation of these DUBs in human gingival fibroblasts (HGFs) upon different stimuli. Methods Immunohist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Osteoclasts from Cyld KO mice were significantly enlarged and exhibited increased activity, resulting in severe osteoporosis (Jin et al, 2008). More importantly, Fu et al (2021) demonstrated that CYLD protein levels were reduced in inflamed gingival tissue samples compared with healthy tissues, suggesting that CYLD might play a critical role in the progression of periodontitis (Fu and Xu, 2021). However, the role of CYLD in the development of periodontitis in vivo remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts from Cyld KO mice were significantly enlarged and exhibited increased activity, resulting in severe osteoporosis (Jin et al, 2008). More importantly, Fu et al (2021) demonstrated that CYLD protein levels were reduced in inflamed gingival tissue samples compared with healthy tissues, suggesting that CYLD might play a critical role in the progression of periodontitis (Fu and Xu, 2021). However, the role of CYLD in the development of periodontitis in vivo remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, HGFs can directly interact with bacteria and their metabolites to participate in the immunoinflammatory response of periodontal tissues and play an essential role in periodontitis progression 25,26) . Although not within the natural category of inflammatory cells, HGFs respond to primary inflammatory signals to induce inflammation to prevent local infection and maintain a modest immunoinflammatory response 27) . Furthermore, dysfunctional fibroblasts may contribute to an ongoing inflammatory response 28) .…”
Section: Introductionmentioning
confidence: 99%